The impact of path dependent degradation on the lifetime of Lithium-Ion batteries - Raj, T (2021)
To ensure lithium-ion batteries are reliable in terms of lifetime and performance, a detailed understanding of their ageing behaviour is essential. Models that predict battery lifetime require knowledge of the causes of degradation and operating conditions that accelerate it. Batteries experience two ageing modes: calendar ageing at rest and cyclic ageing during the passage of current. Existing empirical ageing models treat these as independent, but degradation may be sensitive to their order and periodicity – a phenomenon known as “path dependence”. This empirical study investigates whether interactions between ageing modes can impact the rate of degradation. Eight groups of graphite/NCA 18650 lithium-ion cells were exposed to load profiles consisting of the same ratio of calendar and cyclic ageing applied in various orders. The profiles incorporate different C-rates, cycling methods and calendar ageing conditions, to gain insight into the conditions that encourage path dependent ageing. The data collected indicates that under certain conditions cells exposed to the same amount of calendar/cyclic ageing, but in different orders, can lead to a difference in degradation trends. The divergence in degradation rates is more pronounced when constant current cycling at higher C-rates and is limited when constant voltage steps are incorporated during cycling. Comparing the rate of degradation experienced by cells exposed to combined load profiles versus the degradation predicted using the cumulative empirical model indicates that the cumulative model underestimates the cell lifetime. These findings suggest that including the possible coupling between calendar and cyclic ageing modes can improve the accuracy of lifetime predictions.